Dependence of E-H transition in argon ICP discharges for treatment of organic molecules - Farias,Carlos Eduardo (2017)
ABSTRACT Plasma surface cleaning is an alternative process that aims at the fully removal of organic contaminants on several kinds of materials. Despite its advantages, there are still lacks on the comprehension of the complex relations between plasma-generated species and organic molecules during plasma cleaning. In the present work, a linear alkane (hexatriacontane - C36H74), used as a contaminant model, was exposed to an Argon radiofrequency (RF) inductively coupled plasma (ICP). The by-products from degradation were monitored by optical emission spectroscopy (OES) and residual gas analysis (RGA), to identify the influence of sample positioning on E and H discharge modes regions. The exposition to H-mode discharge resulted in more intense and profuse emissions of C-H and C2 systems. RGA results show similar byproducts from degradation in both modes; however, the intensity from treatment in H-mode is largely greater. It was also observed that plasma etching in H-mode is enough to melt the sample, while E-type discharge leaves the surface of the sample apparently unchanged.